1847 Ind. Acts 93 - (:unkn) unknown (My University, 1847)
An Act to Incorporate the City of Jeffersonville, and the Several Acts Amendatory Thereto Into One Act, and to Amend the Same, chap 77, § 49, pt. 8: Granted the city of Jeffersonville the authority to regulate and license the keepers of gunpowder and other explosive compounds
Keywords: GUNPOWDER - STORAGE